Removal of copper ion (Cu) from aqueous solution by adsorption on pandan leaves Biochar using response surface methodology - Rozman, Luqman Hakim (2018)
This study focused on the adsorption of copper ion utilising pandan leaves biochar as adsorbent. Agricultural waste of pandan leaves transformed into low cost biochar was studied. Batch adsorption studies were carried out to explore the effect of various adsorption parameters which are initial concentration, adsorbent dosage and contact time while the response in this study is copper ion removal (%). The absorbance reading for concentration of copper solution was determined using atomic absorption spectrometer (AAS). The optimisation studies were performed using response surface methodology (RSM). Quadratic model or second-order polynomial containing linear and two factor terms were studied using central composite design (CCD). The correlation coefficient, R2 for the quadratic model was found to be 0.9423. The interactions of the variables were studied using the three dimensional surface graph and contour plot. The optimum conditions predicted by RSM were found to be at initial concentration of 45.94 mg/L, contact time 24.82 minutes, adsorbent dosage 0.05 g; the removal of copper ion up to 99.11% at desirability of 1.0.